Memory and covenant : the role of Israel's and God's memory in sustaining the Deuteronomic and priestly covenants - Ellman, Barat (Emerging scholars., 2013)
Memory and Covenant, combines a close reading of texts in the deuteronomic, priestly, and holiness traditions with analysis of ritual and scrutiny of the different terminology used in each tradition regarding memory. Ellman demonstrates that the exploration of the concept of memory is critical to understanding the overall cosmologies, theologies, and religious programs of these distinct traditions. All three regard memory as a vital element of religious practice and as the principal instrument of covenant fidelity--but in very different ways. Ellman shows that for the deuteronomic tradition, memory is an epistemological and pedagogical means for keeping Israel faithful to its God and God's commandments, even when Israelites are far from the temple and its worship. The priestly tradition, however, understands that the covenant depends on God's memory, which must be aroused by the sensory stimuli of the temple cult. The holiness school incorporates the priestly idea of sensory memory but places responsibility for remembering on Israel. A subsequent layer of priestly tradition revives the centrality of God's memory within a thorough-going theology uniting temple worship with creation.